PENGARUH PAJAK TANGGUHAN DAN PERATAAN LABA TERHADAP PERINGKAT OBLIGASI PERUSAHAAN YANG TERDAFTAR DI BEI - Yandytia Kusuma Aji Damanik, 09.05.52.0141; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2014)
This study aims to examine how the effect of tax deffered and income smoothing to the bond rating. Study sampleas many as 10 manufacturing companies on the Indonesian Stock Exchange. This study is use secondary data by observations period 2010 - 2012, so the number of samples (n) =30. Methods of data collection using documentationâs method of Indonesian Stock Exchange. And the method of data analysis using multiple linear regression. The results showed that tax deffered is significant and negative to the bond rating, the income smoothing is not significant to the bond rating. Keywords: tax deffered, income smoothing, bond rating